Immersive Learning through Audio-Visual Media: Reconstructing Arabic Language Teaching for the Digital Generation - Rizki Meilizia, Dara; Yul, Widiya; Andrian, Riko (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The lack of engaging instructional media in Arabic language education remains a persistent issue in the educational domain. This study aims to examine the extent to which the implementation of audio-visual media, as a response to digital-based learning, has contributed to the improvement of female students’ learning outcomes at Ma’had Al-Jami’ah IAIN Kerinci. Employing a qualitative method with a grounded theory approach, data were collected through observations, interviews, and documentation within the Arabic specialization program that incorporates audio-visual media in its instructional process. The findings reveal that instructional media remain largely dominated by traditional approaches, which have yet to fully accommodate the diverse learning styles of female students. These findings underscore the importance of integrating technology into the learning process in this digital era. The final results of this study indicate that the use of audio-visual-based instructional media in Arabic language education actively contributes to enhancing both student engagement and academic achievement. This is evidenced by a more enjoyable and dynamic learning environment. This research calls on Arabic language educators to optimize the use of digital-based learning media for female students, suggesting that with varied content delivery formats, audio-visual media presents a viable solution for interactive 21st-century learning.